IMPACT OF MATERNAL TOXIC TRACE ELEMENT IMBALANCE ON FETAL GROWTH RESTRICTION AND DEVELOPMENT - Akhrarova Nigora Abdugaparovna; Ismailova Maxfuza Ubaydullaevna; Jamoliddinov Nurmuhammad Jaloliddin o’g’li (Web of Journals Publishing, 2025)
Objective. This study aims to assess how disturbances in maternal trace element balance affect the protective interactions within the mother–placenta–fetus system, potentially leading to delayed fetal development and intrauterine growth restriction. Materials and Methods. Concentrations of the trace elements cobalt (Co), nickel (Ni), and lead (Pb) were analyzed in both the blood serum and erythrocytes of 25 neonates with low birth weight (LBW). These results were compared with a control group of 25 full-term newborns of normal birth weight (NBW) and their mothers. Results. The findings revealed that elevated and unbalanced levels of toxic elements in pregnant women, combined with placental insufficiency, disrupt the metabolism of these elements in both the fetus and newborn. In LBW infants, the observed trace element imbalance correlates with impaired placental transport and storage. Specifically, mothers of these infants had a marked cobalt deficiency and significantly higher levels of lead and nickel in their serum. These changes were associated with perinatal hypoxic damage in the newborns.
Keywords: Placenta, fetus, trace elements, neonatal health.